Management of change—enabler or inhibitor?. Issue 2 (24th April 2013) - Kelly, Brian D.
<x xml:space="preserve">Abstract</x> Management of change (MOC) is one of the more fundamental elements of process safety management (PSM) and one which is common to all PSM frameworks. It is also an activity that breeds frustration and difficulty in many organizations, and this may impede its effectiveness. To address, this concern it is necessary to fully understand the purpose and benefits of MOC, and the efforts required to make it work. This article highlights some of the principal barriers to an effective MOC initiative and suggests ways to streamline it so that it provides optimum benefit. © 2013 American Institute of Chemical Engineers Process Saf Prog, 2013